(untitled) (Nordic Journal of African Studies, 2005)
This paper discusses how Kiswahili teaching can be carried out in a globalised world through the initiative of the Kiswahili-speaking countries of East and Central Africa. It starts by looking at the concept of globalization itself and notes that as a new concept to much of the world a lot of people are still grappling with its meaning. However, it is generally seen as a process of globally linking economic and socio-political aspects by the developed world but could also be carried out by the developing world. The teaching of Kiswahili is seen as an aspect which is already in the process of being globalised by the developed world through the preparations of IT based courses by some Universities in Europe and the US. That is why this paper is urging the initiative of the Kiswahili-speaking countries in this process. It notes, however, that for the latter to undertake such an initiative there are a lot of challenges. If these challenges are surmounted, both Kiswahili and the people of the world stand to benefit academically, socially and economically.